Analisis Efektivitas Penyaluran Pembiayaan Murabahah terhadap Pertumbuhan Laba Bersih: Studi Kasus Bank BJB Syariah KCP Lippo Cikarang - Fahmi Irfanulloh; Mia Lasmi Wardiah (Jurnal Bisnis Inovatif dan Digital, 2025)
This study aims to analyze the effectiveness of murabahah financing distribution on net profit growth at Bank BJB Syariah KCP Lippo Cikarang. The background of the study is based on the importance of murabahah financing as one of the main products of Islamic banks in supporting profit growth, as well as the need to ensure that the distribution of financing runs effectively and has a positive impact on the bank's financial performance. This study uses a qualitative method with a case study approach, where data is collected through in-depth interviews and internal bank documentation. The results of the study indicate that the distribution of murabahah financing at Bank BJB Syariah KCP Lippo Cikarang has been running effectively, marked by a consistent increase in net profit during the study period. This finding indicates that optimizing the murabahah financing distribution process can be an important strategy in increasing the profitability of Islamic banks. The implication of this study is the need to strengthen the financing monitoring and evaluation system so that the effectiveness of distribution is maintained and is able to provide maximum contribution to the growth of the bank's net profit.